The fall of Berlin through the eyes of women. The case of Margret Boveri and Ursula von Kardorff - Fronczak-Chruściel, Paulina (City and War, 2021)
The aim of this article is to present the situation in Berlin in the last months of the Second World War from a perspective of two journalists – Margret Boveri and Ursula von Kardorff. Comparative analysis of two sources should present varied problems of citizens of Third Reich in the final phase of the war – for example – problems with provisioning, power and water outage or difficulties with commuting by public transport. In a context of the above considerations no less important were descriptions of German citizens panic, caused by numerous bombardments and by soldiers of Red Army. The proper considerations were preceded by short characteristics of both authors, including for example: descent, education, career path or approach to politics. Analysis of this information helps to understand both women attitude not only to the situation in Berlin, but also to broadly defined warfare. In order to systemize the narration in the article was presented a short description of the situation at the both fronts in the last months of the war.